Energy Release Rates in Fracture of Dissipative Materials - Dumitrescu, A.T.; Cocu, M. (Engineering Transactions, 1987)
Expressions for the energy release rates in the presence of a propagating crack for a dissipative material are given. The relation between these energy release rates and J-type integrals is shown. This relation is used to calculate the global dissipation during the fracture process.